FUN LEARNING METODE PEMBELAJARAN BARU YANG MENYENANGKAN DALAM DUNIA PENDIDIKAN - Fitriani, Sadyah; Kurniawan, Naufal (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2023)
This journal explains the importance of a learning method carried out by teachers on the level of understanding of students considering that education is an important thing for the future of the nation because education can give birth to the next generation of quality and character.Therefore, with the rapid development of technology from time to time, it must be utilized in the teaching and learning process by creating a new learning method using digital media so that activities can run more easilyKeywords : Learning, Education, School